1997
DOI: 10.1007/pl00005109
|View full text |Cite
|
Sign up to set email alerts
|

Prejunctional modulation by angiotensins of noradrenaline release from sympathetic neurons in isolated rabbit aorta

Abstract: The aims of the present work were to compare the modulating effect of angiotensins I, II, III, IV and (1-7) [AI, AII, AIII, AIV and A(1-7) respectively] on stimulation-evoked noradrenaline release from postganglionic sympathetic nerves in rabbit isolated aorta; to examine the influence of inhibiting the neuronal and extraneuronal uptake of noradrenaline on the modulating effect of AII and thirdly, to determine the role of angiotensin converting enzyme (ACE) in the modulating effects of AI and AII and the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Nitrergic NO can act at pre- and post-synaptic sites to reduce sympathetic transduction at vascular smooth muscle 28. Effects are largest in the splanchnic vasculature29 and in the kidney30 where nitrergic nerve density is greatest.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrergic NO can act at pre- and post-synaptic sites to reduce sympathetic transduction at vascular smooth muscle 28. Effects are largest in the splanchnic vasculature29 and in the kidney30 where nitrergic nerve density is greatest.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence, albeit conflicting, that the sympathetic nervous system is activated by the renin-angiotensin system. [1][2][3][4][5][6][7][8][9][10][11][12][13] This activation supposedly occurs through stimulation of angiotensin II receptors within the central nervous system and/or stimulation of presynaptic angiotensin II receptors located at sympathetic nerve terminals. When investigating the sympathetic nervous system and its interaction with the renin-angiotensin system, the heart is of particular interest.…”
mentioning
confidence: 99%
“…19 -21 In those studies that demonstrated interaction between angiotensin II and the sympathetic nervous system, most evidence points toward direct facilitation mediated by presynaptic angiotensin II type 1 (AT 1 ) receptors resulting in either a classic calcium-dependent augmentation of exocytotic norepinephrine release [1][2][3] or in enhanced nonexocytotic release via activation of the Na ϩ /H ϩ exchanger. 22,23 Therefore, we not only investigated the modulation of NE MIF by angiotensin II under basal conditions but also during enhanced exocytotic norepinephrine release evoked by stimulation of the left stellate ganglion.…”
mentioning
confidence: 99%
“…Ang II induces vasoconstriction or vasopressor response partly due to facilitation of catecholamine release in vertebrate species (Cox et al, 1996;Guimarães et al, 2001;Nishimura, 2001;Storgaard and Nedergaard, 1997). We reported that the hypertensive effect of Ang II in B. jararaca was partly due to catecholamine release (Breno and Picarelli, 1992).…”
Section: Discussionmentioning
confidence: 90%
“…To investigate a local RAS in the aorta of B. jararaca, two main components of the cascade were evaluated: the Ang II receptor and ACE, which is an important rate-limiting step in generating the active peptide Ang II from its inactive form Ang I (Fyhrquist and Saijonmaa, 2008). Moreover, previous studies performed in rabbit and rat arteries have shown that removing the endothelial layer modifies the contractile effect induced by Ang II (Chen et al, 1995;Le Tran and Forster, 1996), and that this peptide also induces vasoconstriction in the arteries of rat, rabbit and dog or vasopressor action in domestic fowl, partly due to the facilitation of catecholamine release (Cox et al, 1996;Guimarães et al, 2001;Nishimura, 2001;Storgaard and Nedergaard, 1997). Therefore, in order to evaluate any modulatory action of the catecholamine and/or endothelium-derived factors on the final Ang II response in B. jararaca, experiments were carried out in the snake aorta pretreated with catecholamine antagonist, and also in the vascular tissue without endothelium.…”
Section: Introductionmentioning
confidence: 96%